A Genetic Risk Score englobing variants associated with coronary artery disease is a good marker for prognosis in an asymptomatic population. (3rd October 2022) - Santos, M; Mendonca, M I; Sa, D; Temtem, M; Sousa, A C; Freitas, S; Rodrigues, M; Henriques, E; Borges, S; Freitas, A I; Guerra, G; Ornelas, I; et al.
Abstract:  : Genome-wide association studies have identified several loci linked to coronary artery disease, and coronary atherosclerosis progression. However, the impact of the genetic contribution to MACE occurrence in sub-clinical atherosclerosis is unknown. Purpose: This study intended to assess the relationship between a set of single nucleotide popymorphism (SNP) associated with CAD by GWAS and the MACE occurrence in an asymptomatic population. After that evaluate whether a wGRS englobing these variants is useful to estimate the prognostic. Methods: Prospective study performed in an asymptomatic cohort from GENEMACOR population-based sample of 1114 subjects aged 51.7±8.3, 74.2 male, without prior coronary artery disease. Coronary Artery Calcium (CAC) score was assessed by coronary computed tomography (Agatston method), and two categories were considered 1–99 and >100. 33 SNP were evaluate to assess the significantly associated with prognostic. A weighted (wGRS) was constructed as the sum of the risk alleles weighted by the corresponding effect size (HR). Cox regression analysis adjusted for the main risk factors, calcium score (CAC) and wGRS to assess the risk of MACE during follow-up. Kaplan Meier assessed the survival. Results: Of the studied 33 SNPs previously associated with CAD (GWAS), only 4 presented the significant association with MACE occurrence: CDKN2B-AS1 rs4977574, HNF4A rs1884613, APOE rs7412/rs429358A and GJA4A rs 618675. After Cox regression analysis the wGRS remained in the equation (HR=2.834); p=0.012, together with CAC score (HR 3.35); p=0.012; diabetes (HR=2.398); p=0.032 and age (HR=1.056; p=0.049. WGRS above the median presented a worst survival rate (p=0.006). Conclusion: The wGRS englobing: CDKN2B-AS1 rs4977574, HNF4A rs1884613, APOE rs7412/rs429358A and GJA4A rs 618675 is independently associated with cardiovascular events in an asymptomatic population. CDKN2B-AS1 rs4977574 gene expression modulates the progression and severity of vascular calcification in vascular smooth muscle cells (VSMCs), HNF1α-AS1 is an important regulatory molecule in cancer biology and cardiovascular disease (its expression may regulate VSMCs, and high expression promotes atheroprotection). More research is crucial for understand prognosis in asymptomatic population. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): SESARAM EPE